Systematic synthetic phonics as the most updated and useful teaching strategy that teachers must use for building up reading skills to first grade students at San Francisco de Asis School - Arcia, Kiara (UDELAS, 2014)
Phonics is a method of teaching children how spoken words are composed of sounds called 'phonemes' and how the letters in words correspond to those phonemes. The process of reading involves decoding or 'breaking' words into separate phonemes, so that meaning can be gained. On the other hand, the process of spelling requires the writer to identify all the phonemes in a word and then use their knowledge of the phonemic code to write or 'make' the word.